Inclusive partnership and community mobilization approaches to improve maternal health care access among internal migrants in nine Indian cities - Bontha V. Babu; Yadlapalli S. Kusuma; Muthusamy Sivakami; Dharmesh K. Lal; Jagjeevan B. Geddam; Anoop Khanna; Monika Agarwal; Godi Sudhakar; Paramita Sengupta; Anna S. Kerketta; Yogita Sharma (Elsevier, 2022)
Background: Disparities in healthcare access to internal migrants exist, and the gaps may widen further if appropriate steps are not taken. Innovative approaches are needed to better align the healthcare services with the migrants' needs. Aim: The aim was to develop and test a supportive strategy of healthcare, which would achieve the desired level of access and delivery of maternal healthcare services to internal migrants living in nine Indian cities. Methods: This intervention with the quasi-experimental design was conducted with pre- vs post-intervention comparisons within the interventional groups and with the control group. The intervention was implemented with an inclusive partnership approach. Advocacy and community mobilization were the main intervention components. Findings: An increased proportion of women sought antenatal care during the intervention. More women initiated seeking antenatal care in the first trimester. Due to intervention, health workers' prenatal (41.7% in the post- against 14.7% in the pre-interventional phase) and postnatal home visits increased (11.6% to 34.7%) considerably. Conclusions: Interventions with inclusive partnership would improve healthcare access to vulnerable communities such as migrants. Hence, efforts to strengthen the government healthcare system through novel strategies are crucial to provide better healthcare to migrants.